AGRISTEC: SMART AGRIVOLTAIC WASTEWATER RECYCLING SYSTEM FOR DECENTRALIZED LOW-CARBON ENERGY BUSINESS IN RURAL AREAS: AN INTEGRATED APPROACH TO SUSTAINABLE AGRICULTURE AND RENEWABLE ENERGY GENERATION - Yajri, Ghifari Jauhar (Jurnal Geosaintek, 2026)
Indonesia’s rural agriculture, particularly in Praya Barat, Lombok, faces critical challenges from unreliable irrigation and centralized diesel-based electricity. Despite high solar potential (5.24 kWh/m²/day), over 6,287 hectares of rice fields suffer from drought, while key water sources are contaminated by domestic and agricultural waste. Limited access to sustainable energy further undermines productivity and food security. The proposed solution, AGRISTEC, a decentralized agrivoltaic wastewater treatment system integrating bifacial PV, solar-powered electrocoagulation, and IoT automation. It consists of a 600W bifacial panel, 72V/100Ah LiFePO₄ battery, MPPT controller, 12V submersible pump, and electrolysis cell managed by an ESP32 microcontroller. Real-time monitoring via TDS, pH, and ORP sensors enables dynamic voltage and flow rate adjustments for irrigation-grade water. System performance was analyzed using HOMER Pro simulation for energy modeling and Excel-based calculations for techno-economic analysis. AGRISTEC generates 8.63 kWh/day and treats up to 960 L/day of wastewater, achieving 99.9% E. coli inactivation and 95% contaminant removal. Lifecycle emissions are reduced to 123.8 gCO₂/kWh over 24.5 times lower than diesel-based alternatives (3,336 gCO₂/kWh). Land-use efficiency is enhanced through vertical APV integration, covering only 12.93 m² per user (45% shading ratio), allowing dual land productivity for food and energy. Cost analysis reveals a 36.8% reduction in total ownership cost compared to diesel-based systems over 25 years. AGRISTEC offers a scalable, low-carbon solution for enhancing water-energy resilience in Indonesia’s underserved agricultural communities.